2020
DOI: 10.1186/s10194-020-01176-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired effective functional connectivity of the sensorimotor network in interictal episodic migraineurs without aura

Abstract: Background Resting-state functional magnetic resonance imaging (Rs-fMRI) has confirmed sensorimotor network (SMN) dysfunction in migraine without aura (MwoA). However, the underlying mechanisms of SMN effective functional connectivity in MwoA remain unclear. We aimed to explore the association between clinical characteristics and effective functional connectivity in SMN, in interictal patients who have MwoA. Methods We used Rs-fMRI to acquire imaging data in 40 episodic patients with MwoA in the interictal p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
4
25
1
Order By: Relevance
“…This suggested that the DMN may not be a neural substrate for the modulation of pain, but also involves a strong affective component. Additionally, Zou et al [34] revealed that an altered DMN function could represent the relief of clinical symptoms, such as the intensity and frequency of headaches following acupuncture, consistent with previous ndings by our research group [25]. Furthermore, a shift in DMN connectivity was illustrated to modulate the pain effect and evaluate the therapeutic effect.…”
Section: M-oa Vs Hcssupporting
confidence: 89%
See 1 more Smart Citation
“…This suggested that the DMN may not be a neural substrate for the modulation of pain, but also involves a strong affective component. Additionally, Zou et al [34] revealed that an altered DMN function could represent the relief of clinical symptoms, such as the intensity and frequency of headaches following acupuncture, consistent with previous ndings by our research group [25]. Furthermore, a shift in DMN connectivity was illustrated to modulate the pain effect and evaluate the therapeutic effect.…”
Section: M-oa Vs Hcssupporting
confidence: 89%
“…Notably, the CEN, including the dorsolateral prefrontal cortex and lateral posterior parietal cortex is crucial for many high-level neurocognitive functions such as cognitive performance, working memory and decision making [13,22,23]. In addition, the MCC is an important component of the cingulate-insular pathway which gates and maintains nociceptive hypersensitivity in the absence of conditioned noxious stimuli [24] and affects the impact of headache in the migraine-free period [25]. Coupled with the aforementioned studies, the current ndings suggest that the visual-related patterns of FC with the CEN and limbic system are associated with cognitive function and top-down regulation of pain.…”
Section: Mwoa-a and Mwoa-oa Vs Hcsmentioning
confidence: 99%
“…Migraine in the interictal period also exhibited altered static functional connectivity in brain regions associated with nociceptive/antinociceptive processing [9,11,[18][19][20][21] as well as functional networks such as dorsal attention and executive control network [22,23]. This functional connectivity analysis typically assumes that functional coupling between brain regions is constant across time.…”
Section: Introductionmentioning
confidence: 99%
“…By means of RS-fMRI ICA approach, a plethora of studies have been conducted to investigate the cognitive networks in order to understand the bidirectional relationship between pain experience and cognitive, affective and emotional dysregulation. The DMN is a well-known network highly relevant for self-referential cognitive processes, involved during stressful experiences, and coping strategies which are important to promote adaptation widely investigated in migraine patients, with apparently conflicting results so far [ 36 , 37 ]. Indeed, several investigations supported a decreased FC within the DMN anterior nodes (e.g., superior temporal gyrus and medial prefrontal cortices), all involved in perception and judgments of internal/external stimuli and in dealing with stressful experiences by the selections of appropriate adaptive and emotional responses in patients with MwoA.…”
Section: Fmrimentioning
confidence: 99%